EFFECT OF OVERWEIGHT AND OBESITY ON LEFT VENTRICULAR FUNCTION RECOVERY IN PATIENTS WITH SEVERE AORTIC STENOSIS AFTER SURGICAL AORTIC VALVE REPLACMENT - Zafirovska, Planinka; Ismail, Ljubica Georgievska; Matveeva, Niki; Mitrev, Zan (Journal of Morphological Sciences; Vol 1 No 2 (2018): JMS, 2018)
Abstract The aim of the study was to assess the effect of body mass index (BMI) on myocardial function and mechanics among patients with severe aortic stenosis (AS) admitted for surgical aortic valve replacement (SAVR). The dramatic increase in the prevalence of obesity and its strong association with cardiovascular disease have resulted in growing interest in understanding the effects of obesity on the cardiovascular hemodynamics and mechanics especially in circumstances of valvular diseases. A total of 51 consecutive patients (age: 65.8Â±9.6 y, 58.8% male,41.2% females) who underwent SAVR for severe AS were classified according to World Health Organization criteria such as normal weight, overweight, or obesity according to their BMI (18.5 to 24.9 kg/m2, 25.0 to 29.9 kg/m2, and â‰¥30.0 kg/m2, respectively). Out of all, 31.4% were obese and 43.1% overweight, with more frequent history of atherosclerotic risk factors. Obese and overweight patients after SAVR showed in comparison to those with normal weight insignificantly smaller indexed aortic valve area (AVAi), higher indexed left atrial volume (LAVI) and left ventricular (LV) end-systolic dimension, lower LV ejection fraction (EF) as well as higher LV filling pressure (E/e`average) as a marker of diastolic dysfunction. In addition, obese patients showed significantly (p=0.008) the highest value of valvuloarterial impedance (Zva) and with borderline significance lowest GLS% (more positive value). Linear regression analysis  showed that BMI adjusted to age, gender and history of hypertension appeared as independent significant predictor of higher Zva value (b=0.136; 95%CI 0.65 to 0.207; p=0.0001) and along with male gender of worse (more positive) LV GLS% values (b=0.314; 95%CI 0.098 to 0.531; p=0.005) after SAVR. BMI appears as independent predictor of more extensive impairment of myocardial function and mechanics after SAVR that could contributed to more unfavorable long-term outcome in these patients. Key words: body mass index, obesity, overweight, severe aortic stenosis, surgical aortic valve replacement, echocardiography, subclinical left ventricular function